2018
DOI: 10.3389/fphys.2018.01839
|View full text |Cite
|
Sign up to set email alerts
|

Forced Swim Reliability for Exercise Testing in Rats by a Tethered Swimming Apparatus

Abstract: To assess the physical capacity of rats in forced swim tests, the animal should perform a continuous activity (CON) at the surface to avoid apnea. Bobbing movement (BOB), vigorous paddling known as climbing (CLI), and diving activity (DIV) are inadequate swimming patterns known to increase the exercise intensity variability, impairing the test reliability. Thus, the exercise work accomplished and related physiological variables, such as the blood lactate concentration, may be unreproducible in forced swim. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…To study exercise‐induced damage, several animal models have been reported, such as the forced swimming test and voluntary wheel running. [ 44 , 45 ] This study employed high‐intensity running as a model because we observed stable gastrointestinal damage caused by running at speeds above the lactate threshold. [ 4 , 29 , 30 ] The intestinal damage was caused by oxidative stress, resulting in the spread of LPS in blood by increasing the leakiness of the intestinal wall (Figure 2 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…To study exercise‐induced damage, several animal models have been reported, such as the forced swimming test and voluntary wheel running. [ 44 , 45 ] This study employed high‐intensity running as a model because we observed stable gastrointestinal damage caused by running at speeds above the lactate threshold. [ 4 , 29 , 30 ] The intestinal damage was caused by oxidative stress, resulting in the spread of LPS in blood by increasing the leakiness of the intestinal wall (Figure 2 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rats are subjected to anaerobic exercise. To do this, use a treadmill for rats at a speed of 35 m/min −1 , 20 min [ 177 ], or swimming [ 178 ]. After the experiments, the correlation of HIF-1α and VEGF in brain tissues after anaerobic exercise was tested in rats.…”
Section: Methodology Of Literature Search and Selectionmentioning
confidence: 99%
“…Moreover it commonly aims to stimulate physical effort and energy expenditure able to influence physiological parameters. These are dependent from the species swimming pattern, protocol intensity and associated methods to generate better reliability and reproducibility in the outcomes (dos Reis et al, 2018). Additionally, a constant performance during training session from the animal, suited for the physiological parameters evaluated and with excessive stress and fatigue avoided are points desired in most methods.…”
Section: Introductionmentioning
confidence: 99%